Depletion the human costs of caring - Rai, Shirin 1960- (Oxford University Press, 2024)
Shirin M. Rai examines the human costs of caring and how these are reproduced across the boundaries of class, race, gender, and generation. Including case studies from different parts of the world and building on various methodologies, Rai looks at the costs of care work, or what she calls 'social reproduction' in several forms. Chapters examine the costs of commuting to work, the value of unpaid work performed by women of different classes, the costs of household work performed by children, and the costs to communities when local economies are challenged by corporate interests
Keywords: Hauspflege; Wirtschaftliche Lage; Caregivers / Social conditions; Caregivers / Economic conditions; Aidants naturels / Conditions sociales; Aidants naturels / Conditions économiques